Characterization of an olfactory system dysfunction model: a vanadium dose-effect study via nose-to-brain delivery in rats - Pereira, Margarida; Venâncio, Carlos; Pinto, Maria Lurdes; Félix, Luís Manuel; Alves-Pimenta, Sofia; Colaço, Bruno (Frontiers in Neuroanatomy, 2025)
IntroductionThe olfactory system acts as an interface between the environment and the brain. Its direct neural connection makes it a target for xenobiotics and a suitable model for studying olfactory dysfunction and related neurotoxic effects. This study aimed to characterize an animal model of olfactory dysfunction induced by nose-to-brain (NTB) delivery of vanadium pentoxide (V2O5).MethodsRats received 182 or 273 μg intranasally, thrice weekly over 4 weeks, followed by behavioral, histological, and biochemical analysis of the olfactory epithelium (OE), olfactory bulbs (OBs), and hippocampus.ResultsBehavioral tests showed significant olfactory deficits, longer latencies, and reduced investigation times in exposed groups. Histological analysis revealed coagulative necrosis in the OE, disrupted cellular organization, reduced number and size of OB glomeruli, and hippocampal neuronal loss with gliosis. Immunohistochemistry revealed increased proliferating cell nuclear antigen (PCNA) expression in the OE, dopaminergic neuron loss and astroglial proliferation in the OB, and hippocampal astroglial proliferation at the highest dose. Myelin basic protein (MBP) expression remained unchanged. Oxidative stress markers were largely unaltered, except for increased superoxide dismutase (SOD) in OBs and glutathione S-transferase (GST) in the hippocampus, especially at the high dose.DiscussionThe results reveal dose-dependent vanadium-induced neurotoxicity in the olfactory system. The higher dose induced pronounced structural damage, neuroinflammation, and oxidative stress, resulting in olfactory and cognitive impairments relevant to advanced olfactory dysfunction and neurodegeneration. The lower dose induced milder yet significant effects, supporting its use in early-stage dysfunction studies. This NTB-based model offers a valuable tool for investigating olfactory dysfunction mechanisms in toxicological and neurodegenerative contexts.